2022
DOI: 10.3390/life12101638
|View full text |Cite
|
Sign up to set email alerts
|

Let-7 microRNAs Are Possibly Associated with Perineural Invasion in Colorectal Cancer by Targeting IGF Axis

Abstract: Increased insulin-like growth factor (IGF) axis activity is associated with the development and progression of different types of malignancies, including colorectal cancer (CRC). MicroRNAs (miRNAs) belonging to the let-7 family have been reported to target genes involved in this axis and are known as tumor suppressors. In this study, in silico bioinformatic analysis was performed to assess miRNA–mRNA interactions between eight miRNAs belonging to the let-7 family and genes involved in the IGF signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…In current study, we hypothesize that hsa-let-7c-5p may serve as a potential regulator of HMMR expression, which was down-regulated in tumour tissues and associated with a favourable prognosis. This aligns with previous research conducted by Andrei et al, who demonstrated that hsa-let-7c-5p inhibits colorectal cancer invasion by targeting the IGF axis (37).…”
Section: Moreover the Clinical Application Values Of Hmmr In Hcc Wassupporting
confidence: 92%
“…In current study, we hypothesize that hsa-let-7c-5p may serve as a potential regulator of HMMR expression, which was down-regulated in tumour tissues and associated with a favourable prognosis. This aligns with previous research conducted by Andrei et al, who demonstrated that hsa-let-7c-5p inhibits colorectal cancer invasion by targeting the IGF axis (37).…”
Section: Moreover the Clinical Application Values Of Hmmr In Hcc Wassupporting
confidence: 92%
“…High expression of hsa-let-7e-5p and hsa-miR-98-5p was associated with a long survival time, while high expression of hsa-miR-221-3p, hsa-miR-222-3p, hsa-miR-380-5p, and hsa-miR-485-5p was associated with a shorter survival time. At the same time, some studies have shown that these miRNAs are related to pan-cancer cell proliferation, migration, and immune infiltration [40][41][42][43]. These results indicate that miRNAs play an important role in the regulation of pan-cancer prognosis.…”
Section: Co-expression Network Of Tp53mentioning
confidence: 86%
“…Contrary to this trend, other members of the let-7 family, such as hsa-let-7f-5p and hsa-let-7i-5p, were found upregulated in the non-responders group. Niculae et al have also reported that both of these miRNAs were also found downregulated in 25 tumoral tissues compared with the corresponding adjacent peritumoral tissues, suggesting that they may possibly be associated with perineural invasion in CRC by targeting the insulin-like growth factor (IGF) signaling system [71]. As stated before, the horizontal hypothesis that miRNA families exhibit a common fashion in different phenotypic cancer environments has already been challenged by Dhawan et al, underlining the autonomous behavior of a single miRNA, regardless of its grouping by family [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, let-7 family members, namely hsa-let-7c-5p, hsa-let-7d-5p, and hsalet 7a-5p, exhibited significantly lower expression levels in non-responders compared to the control group in our study. Members of the let-7 family are known tumor suppressors [71] that modulate oncogenes such as HMGA2 [72], MYC [73] and RAS [74]. Danac et al suggested that circPVT1 upregulates NRAS by inhibiting let-7 and thus promotes oncogenic phenotypes in CRC cells [75].…”
Section: Discussionmentioning
confidence: 99%